Efisiensi Alokatif Usahatani Jagung Pipil Di Desa Bange Kecamatan Sanggau Ledo Kabupaten Bengkayang - Fradita Dies; Erlinda Yurisinthae; Marisi Aritonang (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
This study aims to analyze the allocative efficiency of shelled corn farming in Bange Village, Sanggau Ledo District, Bengkayang Regency. Location selection is done intentionally. Data collection was obtained from the results of direct interviws with farmers with the help of a list of questions in the form a questionnaire. The analytical method used is the analysis of Cobb-Dauglas production function and allocative efficiency analysis. The results showed that the variables in the form of land area, seeds, labor, manure, urea fertilizer, NPK fertilizer, and gramaxone had an effect on the production of shelled corn. The level of allocative efficiency on the variables of land area, seeds, labor, manure, urea fertilizer, NPK fertilizer, and gramaxone have not been efficient.